SISTEM PAKAR PENGENALAN TIPE KEPRIBADIAN MAHASISWA TERHADAP KEMATANGAN PILIHAN PROFESI - Mazia, Lia; Ahmad, Fadhillah (LPPM Universitas Nusa Mandiri, 2012)
Expert Systems in Introduction of the Personality Type is an expert system designed as a tool to diagnose personality type with a dynamic knowledge base. This knowledge is obtained from various sources including research by experts in the field as well as books related to personality. Expert system method used is forward chaining. This expert system will display a selection of personality profile options that can be selected by the user, in which each option will bring the user's personality profile to get the final result. In the end, the system will display the results of the introduction of personality type and other details. The system is developed using Microsoft Visual Basic 6.0. Conclusions obtained in this study is that the expert system is designed to help make decisions that will be undertaken profession.